Endoscopic epitympanic exploration in mucosal chronic otitis media: is canal wall up mastoidectomy really needed?. Issue 1 (25th January 2021) - Das, A; Mitra, S; Hazra, S; Sengupta, A
Abstract: Objective: To compare endoscopic epitympanic exploration with conventional canal wall up (cortical) mastoidectomy for mucosal chronic otitis media in terms of post-operative outcomes. Methods: Seventy-six patients diagnosed with chronic otitis media (mucosal variety) were randomly assigned to two treatment groups: endoscopic epitympanic exploration and conventional canal wall up (cortical) mastoidectomy. The groups were compared in terms of: post-operative anatomical outcomes (graft uptake), middle-ear physiological outcomes (post-operative tympanometry), audiological outcomes (air–bone gap), surgical time, post-operative pain, vertigo, and long-term complications such as retraction pocket and re-perforation. Results: There was a statistically significant difference between the groups in terms of mean air–bone gap at 12 months, surgical time, and median post-operative pain measured at 6 hours ( p < 0.05). No statistically significant differences were noted in terms of: graft uptake at 1, 3 and 6 months, mean air–bone gap at 3 and 6 months, tympanometry at 3, 6 and 12 months, vertigo at 1 week, or long-term complications. Conclusion: Endoscopic epitympanic exploration resulted in significantly better long-term audiological outcomes, shorter operating time and less pain compared with conventional canal wall up (cortical) mastoidectomy.